2019
DOI: 10.1186/s12904-019-0456-z
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of randomized controlled trials of palliative care for pain among Chinese adults with cancer

Abstract: Background Pain is one of the most common symptoms that has a severe impact on quality of life and is associated with numerous psychosocial issues in cancer patients. Palliative care, which is a recent development in China, mainly focuses on symptom control and provides psychosocial support in order to improve quality of life for terminally ill patients. This meta-analysis aimed to evaluate the effects of palliative care on cancer pain in China. Methods The four most co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…Pain is probably the most common and distressing symptom in the terminal phase of cancer [ 10 , 16 ], resulting in the particularly high priority of pain management (PM) around the research and practice of PC. Our meta-analysis showed that PC was largely effective for relieving cancer pain [ 17 ]. Due to multi-factorial adverse impacts of cancer pain, the beneficial effects of PM should consider not only biomedical factors but also patients’ psychosocial and spiritual distress [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pain is probably the most common and distressing symptom in the terminal phase of cancer [ 10 , 16 ], resulting in the particularly high priority of pain management (PM) around the research and practice of PC. Our meta-analysis showed that PC was largely effective for relieving cancer pain [ 17 ]. Due to multi-factorial adverse impacts of cancer pain, the beneficial effects of PM should consider not only biomedical factors but also patients’ psychosocial and spiritual distress [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, another review indicated that when conventional cancer care was complemented by acupuncture and related therapies there was an improvement in QoL, with reduced pain and fatigue [ 21 ]. In another review [ 22 ] a preliminary conclusion was that PC effectively relieves pain in patients with cancer. However, this review covered only a small number of studies ( n = 18) with several methodological limitations and exhibited a high heterogeneity of both pharmacological and non-pharmacological treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Palliative care (PC) has been shown to improve patients' QOL through mitigation of disease‐, treatment‐, and psychosocial‐related symptoms 7–12 . Some studies have even suggested a survival benefit to receiving PC for certain cancers 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Palliative care (PC) has been shown to improve patients' QOL through mitigation of disease-, treatment-, and psychosocial-related symptoms. [7][8][9][10][11][12] Some studies have even suggested a survival benefit to receiving PC for certain cancers. 13 For stage IV HCC, a survival benefit has been shown with the receipt of palliative radiotherapy.…”
mentioning
confidence: 99%